2018
DOI: 10.1016/j.psychsport.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and alternate action observation and motor imagery combinations improve aiming performance

Abstract: Motor imagery (MI) and action observation (AO) are techniques that have been shown to enhance motor skill learning. While both techniques have been used independently, recent research has demonstrated that combining action observation and motor imagery (AOMI) promotes better outcomes. However, little is known about the most effective way to combine these techniques. This study examined the effects of simultaneous (i.e., observing an action whilst imagining carrying out the action concurrently) and alternate (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 49 publications
5
69
0
4
Order By: Relevance
“…Fifty university students (25 males, 25 females; Mean age = 28.80 years, SD = 6.75) were recruited. The number of participants was established to be comparable to that of previous research of a similar nature . All participants reported being right‐handed using the Edinburgh Handedness Inventory and reported normal or corrected to normal vision and were novice performers who had limited dart‐throwing experience.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fifty university students (25 males, 25 females; Mean age = 28.80 years, SD = 6.75) were recruited. The number of participants was established to be comparable to that of previous research of a similar nature . All participants reported being right‐handed using the Edinburgh Handedness Inventory and reported normal or corrected to normal vision and were novice performers who had limited dart‐throwing experience.…”
Section: Methodsmentioning
confidence: 98%
“…While some research on stroke patients and postsurgical orthopedic patients has suggested that combining AOMI in a simultaneous manner enhances functional outcomes, a recent study using a sporting task has suggested that the manner in which AO and MI are combined has little bearing on the magnitude of motor learning witnessed. Specifically, Romano‐Smith, Wood, Wright, & Wakefield employed a 6‐week intervention where one group was instructed to observe while simultaneously completing concurrent MI movement (S‐AOMI), while the other group practiced AOMI by alternating AO and MI components (A‐AOMI). Results showed that both AOMI combinations improved significantly more than participants in the AO and MI only groups when learning dart‐throwing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Eaves, Riach, Holmes, and Wright (2016), AO evokes a cognitive representation of the observed action, involving bottom-up and percept-driven processes that are under the subconscious control of the observer (Holmes & Calmels, 2008). The beneficial effect of AO seems to reflect involuntary activation of motor codes corresponding to observed motor Motor Imagery, Video and Basket-ball 5 actions (Romano- Smith, Wood, Wright, & Wakefield, 2018). During AO, observers copy the movement kinematics (e.g., speed) of the model, which is coded trough biological motion (Wild, Poliakoff, Jerrison, & Gowen, 2010).…”
mentioning
confidence: 99%
“…Other authors have suggested using AO combined with MI to improve motor execution and performance (Battaglia et al, 2014;Robin & Flochlay, 2017;Romano-Smith et al, 2018;Taube, Lorch, Zeiter, & Keller, 2014). AO and MI are two forms of motor simulation that activate the motor system in the absence of overt motor execution (Eaves et al, 2016;Jeannerod, 2001) and evoke an internal motor representation of the movement (Rizzolatti & Sinigaglia, 2010).…”
mentioning
confidence: 99%